Socioeconomic Conditions of Apple Growers in Marpha, Mustang District (RR Interdisciplinary Journal, 2023)
Socio-economic condition of the farmers plays a crucial role in agriculture. Apple is one of the key fruits with potential to generate income and employment in the high mountain districts of western Nepal. The objective of the study has to analyze the socioeconomic status of apple grower in Marpha of Mustang district. A total of 145 households have been sampled out of 235 households by using simple random sampling technique and interviewed with a semi-structured questionnaire to obtain data regarding socioeconomic condition, production, marketing channels, cost and apple price from apple growers as well as secondary sources of data obtained from the District Agriculture Development Office and Temperate Horticulture Development Center, Marpha, Mustang with other published and unpublished documents. The study concluded that socioeconomic conditions of marginal farmers have significantly improved during the last three decades because of apple farming. Seasonal road and poor marketing infrastructure, underprivileged technical knowledge, unavailability of inputs in time, insect pest damage and lack of storage facilities, price disparity and low quantity of production have been noticed major production and marketing problems in the study area.